Fluid and White Matter Suppression Imaging and Voxel-Based Morphometric Analysis in Conventional Magnetic Resonance Imaging-Negative Epilepsy - Sun, Ke; Yu, Tao; Yang, Dongju; Ren, Zhiwei; Qiao, Liang; Ni, Duanyu; Wang, Xueyuan; Zhao, Yongxiang; Chen, Xin; Xiang, Jing; Chen, Nan; Gao, Runshi; et al. (Frontiers in Neurology, 2021)
Purpose: Delineation of subtle lesions in magnetic resonance imaging (MRI)-negative patients is of great importance in the preoperative epilepsy evaluation. The aims of our study were to explore the diagnostic value of the novel fluid and white matter suppression (FLAWS) sequence in comparison to a voxel-based MRI post-processing morphometric analysis program (MAP) in a consecutive cohort of non-lesional patients. Methods: Surgical candidates with a negative finding on an official neuroradiology report were enrolled. High-resolution FLAWS image and MAP maps generated based on high-resolution three-dimensional (3D) T1 image, were visually inspected for each patient. The findings of FLAWS or MAP- positive (FLAWS/MAP+) regions were compared with the surgical resection cavity in correlation with surgical outcome and pathology. Results: Forty-five patients were enrolled; the pathological examination revealed focal cortical dysplasia (FCD) in 32 patients and other findings in 13 patients. The positive rate, sensitivity, and speciﬁcity were 48.9%, 0.43, and 0.87, respectively, for FLAWS and 64.4%, 0.57, and 0.8, respectively, for MAP. Concordance between surgical resection and FLAWS+ or MAP+ regions was significantly associated with a seizure-free outcome (FLAWS: p = 0.002; MAP: p = 0.0003). Positive finding in FLAWS and MAP together with abnormalities in the same gyrus (FLAWS-MAP gyral+) was detected in 31.1% of patients. FLAWS+ only and MAP+ only was found in 7 (15.5%) and 14 (31.1%) patients, respectively. Conclusions: FLAWS showed a promising value for identifying subtle epileptogenic lesions and can be used as a complement to current MAP in patients with MRI-negative epilepsy.